Identification of an anti-CRISPR protein that inhibits the CRISPR-Cas type I-B system in Clostridioides difficile - Muzyukina, Polina; Shkaruta, Anton; Guzman, Noemi M.; Andreani, Jessica; Borges, Adair L.; Bondy-Denomy, Joseph; Maikova, Anna; Semenova, Ekaterina; Severinov, Konstantin; Soutourina, Olga (mSphere, 2023)
CRISPR-Cas systems provide prokaryotic hosts with adaptive immunity against mobile genetic elements. Many bacteriophages encode anti-CRISPR (Acr) proteins that inhibit host defense. The identification of Acr proteins is challenging due to their small size and high sequence diversity, and only a limited number has been characterized to date. In this study, we report the discovery of a novel Acr protein, AcrIB2, encoded by the φCD38-2 Clostridioides difficile phage that efficiently inhibits interference by the type I-B CRISPR-Cas system of the host and likely acts as a DNA mimic. Most C. difficile strains contain two cas operons, one encoding a full set of interference and adaptation proteins and another encoding interference proteins only. Unexpectedly, we demonstrate that only the partial operon is required for interference and is subject to inhibition by AcrIB2. Clostridioides difficile is the widespread anaerobic spore-forming bacterium that is a major cause of potentially lethal nosocomial infections associated with antibiotic therapy worldwide. Due to the increase in severe forms associated with a strong inflammatory response and higher recurrence rates, a current imperative is to develop synergistic and alternative treatments for C. difficile infections. In particular, phage therapy is regarded as a potential substitute for existing antimicrobial treatments. However, it faces challenges because C. difficile has highly active CRISPR-Cas immunity, which may be a specific adaptation to phage-rich and highly crowded gut environment. To overcome this defense, C. difficile phages must employ anti-CRISPR mechanisms. Here, we present the first anti-CRISPR protein that inhibits the CRISPR-Cas defense system in this pathogen. Our work offers insights into the interactions between C. difficile and its phages, paving the way for future CRISPR-based applications and development of effective phage therapy strategies combined with the engineering of virulent C. difficile infecting phages.